Analisis Pengaruh Modal Manusia dan Penggunaan Teknologi Informasi Komunikasi (TIK) Terhadap Pengembalian Pendidikan Di Indonesia - Nur Haminati; Neng Kamarni (LP. Ma'arif Janggan Magetan, 2023)
This study aim to determine the return to education in Indonesia analyzed based on various types of education as well as the influence of human capital and ICT use. Method used to analyze is the Mincerian Earning Function with the Heckman Two Step approach. We use micro data from the March 2021 National Socioeconomic Survey obtained from the Indonesian Central Bureau of Statistics. We found increasing years of school will increase the return to education just as work experience will increase the return of education, but increasing work experience will lead to a decrease in return on education. Individual characteristics, namely the male population with unmarried status, residing in urban areas, working in secondary business fields and the formal sector and with full working hours will increase the return on education. Health variables that cause a decrease in education returns as a result of the COVID-19 pandemic conditions in Indonesia. The return of general education and vocational education, and non-formal education is higher than madrasah education or Islamic education. The use of computers and the Internet for economic activity purpose provides excellent value for increasing educational returns.